The power of pyramid decomposition in Normaliz. (May 2016) - Bruns, Winfried; Ichim, Bogdan; Söger, Christof
Abstract: We describe the use of pyramid decomposition in Normaliz, a software tool for the computation of Hilbert bases and enumerative data of rational cones and affine monoids. Pyramid decomposition in connection with efficient parallelization and streamlined evaluation of simplicial cones has enabled Normaliz to process triangulations of size ≈ 5 ⋅ 10 11 that arise in the computation of Ehrhart series related to the theory of social choice.